Efeito de uma bebida probiótica (Enterococcus faecium CRL 183 e Bifidobacterium longum ATCC 15707) à base de extrato aquoso de soja no desenvolvimento de colite quimicamente induzida em ratos - Celiberto, Larissa Sbaglia [UNESP] (2014)
Inflammatory bowel disease (IBD), including Crohn's disease (CD) and ulcerative colitis (UC), comprise a group of disorders and their main characteristic is an inflammation of the intestinal mucosa. Although its origin is not yet fully known, there is growing evidence linking genetics predisposition, composition of the intestinal microbiota and immune system factors as precursors for the initiation and progression of these pathologies. The use of certain probiotic microorganisms has been considered as promising way to reduce the risk of inflammatory bowel disease, specifically ulcerative colitis. Several mechanisms have been proposed to explain the benefits of probiotics, indicating that some bacterial strains are able to positively modulate the intestinal microbiota and the immune system, and produce metabolites with anti-inflammatory capacity. As the effects and the mechanisms involved are strain-specific, further studies are extremely important to understand the interactions between gut microbiota and host, contributing to the knowledge on therapeutic potential of probiotics in diseases related to dysbiosis. This current paper aims to bring together the various results and information based on scientific evidence that are related to probiotics and the inflammatory bowel disease, with emphasis on the possible mechanisms involved in this action. Furthermore, the effects of daily ingestion of a product based on an aqueous extract of soybean, fermented by Enterococcus faecium CRL 183 and Lactobacillus helveticus 416 with the addition of Bifidobacterium longum ATCC 15707, were also investigated on chemically induced colitis in rats. Colitis was induced by 4% dextran sulfate sodium (DSS), dissolved in the drinking water supplied to the animal, which was ingested daily for a period of seven days. The animals will then be assigned randomly to four groups (n=10): Group C: healthy animals that do not receive the products under study; Group CL: ...